Managing the Aftermath of a Fire on Intensive Care Caused by an Oxygen Cylinder. (October 2014) - Kelly, Fiona E; Hardy, Rowan; Cook, Tim M; Nolan, Jerry P; Craft, Tim; Osborn, Mike; Bedor, Cindi; Hunt, Julian
In 2011, a fire broke out on our intensive care unit. An oxygen cylinder caught fire as it was turned on and spread to the mattress of the bed on which it was laid, the bedding, the patient on the bed, the curtains around the bed, the flooring beneath it and the ceiling above. The patient was dragged to safety and the fire put out by two doctors using five fire extinguishers. The unit was filled with smoke within seconds. Ten other patients on the ICU at the time were evacuated within seven minutes, and a patient in a side room (who was not immediately affected) 30 minutes later. We discuss the event, the evacuation, how the aftermath of the fire was managed by the hospital staff, and the changes put in place to improve fire safety locally and nationally.